Cardamonin suppresses mTORC1/SREBP1 through reducing Raptor and inhibits de novo lipogenesis in ovarian cancer - Peiguang Niu; Danyun Li; Huajiao Chen; Yanting Zhu; Jintuo Zhou; Jinhua Zhang; Ying Liu (PLoS ONE, 2025)
Metabolic reprogramming is a hallmark of cancer and de novo lipogenesis (DNL) accelerates the progression of ovarian cancer. In this study, we investigated the effects of cardamonin, a natural compound potential to suppress various malignancies, on the lipid anabolism in ovarian cancer. Cell proliferation was assessed using CCK-8 and clone formation assay. Cell apoptosis was detected by flow cytometry with Annexin V-FITC/PI staining and mitochondrial membrane potential (MMP) was measured with JC-10 probe. Free fatty acids (FFA) was measured by fluorescence using acyl-CoA oxidation and carnitine palmitoyl transferase-1 (CPT-1) activity was analyzed by spectrophotometric assay using palmitoyl-CoA and DTNB (5,5’-dithio-bis-(2-nitrobenzoic acid)) reaction. mRNA expression was measured by Quantitative Real-Time PCR. Protein expression was analyzed through western blotting and immunofluorescence. Raptor was knocked down by shRNA and Raptor was overexpressed by lentiviral transfection. The antitumor effect of cardamonin was evaluated using a xenotransplantation tumor bearing mouse model. Cardamonin suppressed the cell proliferation, induced cell apoptosis and triggered mitochondrial damage in ovarian cancer cells. Cardamonin inhibited the protein expression of sterol regulatory element binding protein 1 (SREBP1) and its downstream lipogenic enzymes and decreased FFA content and CPT-1 activity. Additionally, cardamonin inhibited the activation of mechanistic target of rapamycin complex 1 (mTORC1) and expression of regulatory-associated protein of mTOR (Raptor). Raptor knockdown abolished the inhibitory effect of cardamonin on mTORC1 and SREBP1. Furthermore, cardamonin inhibited mTORC1 activation and lipogenic proteins expression induced by Raptor overexpression. Cardamonin reduced the tumor growth and fatty acid synthase of the tumors, as evidenced by decreased expression of Ki-67 and FASN. It suggests that cardamonin suppresses mTORC1/SREBP1 through reducing the protein level of Raptor and inhibits DNL of ovarian cancer.